Perilous bounty : the looming collapse of American farming and how to prevent it - Philpott, Tom (Food writer) (Bloomsbury Publishing, 2020)
An unsettling journey into the United States' disaster-bound food system, and an exploration of possible solutions, from leading food politics commentator and farmer-turned-journalist Tom Philpott.